Emergency blood transfusion service and cold storage refrigeration : inter-departmental correspondence - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1939-11-03 1939 1930s 2 pages I.C.3. TRADES UNION CONGRESS. INTER-DEPARTMENTAL CORRESPONDENCE. From......................................Department... To... Date... 3rd November, 1939. SUBJECT. BLOOD TRANSFUSION AND REFRIGERATION contd:- - 2 - administered, was in many a period invaluable and saved very many lives. When it is badly performed, of course — performed with blood that is not properly stored — blood transfusion is not without its danger, and this is why it is so essential that the cold stroage [storage] of blood to be transfused in emergency medical work in Great Britain should be properly equipped and properly organised, so that the service may suffer from no difficulties from previous bad organisation and poor storage. 5. I think the comments made about domestic type refrigerators, as applicable to the cold storage of blood, are true, and seem to me on sound ground, and I personally would like to support the view that blood storage refrigerators should be secured for every Centre and for every Hospital in the country as soon as possible. The one thing I am not certain about is, that in this case this document has been obviously written with the object of selling products of one special firm. I am not sufficiently conversant with the differences in the different refrigerators to say that any one particular product of one special firm is better than another. The Frigidaire Company, of course, has a name and is well known, but I cannot imagine that other firms making refrigerators could not also make special refrigerators for blood storage. But I again emphasise that the refrigerators for blood storage should be different to those of the domestic type. They should be manufactured in a particular way for this special purpose. I propose, if you approve, to speak unofficially to blood storage authorities, like Dr. Janet Vaughan, who is now in charge of the Blood Storage in Slough, and to have a word with Professor J.B.S. Haldane. HBM/EKK/59. 292/845.2/4/50